FKBP25 Regulates Meiotic Apparatus During Mouse Oocyte Maturation - Wang, Danni; Sun, Hongzheng; Zhang, Jiaqi; Huang, Zhenyue; Li, Congyang; Han, Longsen; Xin, Yongan; Tang, Shoubin; Ge, Juan; Wang, Qiang (Frontiers in Cell and Developmental Biology, 2021)
FK506 binding proteins 25 (FKBP25) has been shown to function in ribosome biogenesis, chromatin organization, and microtubule stability in mitosis. However, the role of FKBP25 in oocyte maturation has not been investigated. Here, we report that oocytes with FKBP25 depletion display abnormal spindle assembly and chromosomes alignment, with defective kinetochore-microtubule attachment. Consistent with this finding, aneuploidy incidence is also elevated in oocytes depleted of FKBP25. Importantly, FKBP25 protein level in old oocytes is significantly reduced, and ectopic expression of FKBP25 could partly rescue the aging-associated meiotic defects. In addition, by employing site-specific mutagenesis, we identify that serine 163 is a major, if not unique, phosphorylation site modulating the action of FKBP25 on meiotic maturation. In summary, our data indicate that FKBP25 is a pivotal factor for determining oocyte quality, and may mediate the effects of maternal aging on female reproduction.